DMAV in Drinking Water Activated NF-κB Signal Pathway and Increased TGF-β and IL-1β Expressions in Bladder Epithelial Cells of Rats - Siqi Cao; Shengnan Liu; Fei Wang; Jieyu Liu; Mengdan Li; Chen Wang; Shuhua Xi (Hindawi Limited, 2015)
Dimethylarsinic acid (DMAV) is the main product of arsenic methylation metabolism in vivo and is rat bladder carcinogen and tumor promoting agent. In this study, we measured the expressions of mRNA and proteins of NF-κB pathway members, IKKα, IKKβ, p65, and p50 in rat bladder epithelium by qRT-PCR and immunohistochemical analysis after rats received drinking water containing 100 and 200 ppm DMAV for 10 weeks. Transforming growth factor-β (TGF-β) immunoexpression in rat bladder epithelium and urine level of IL-1β also were determined. We found that DMAV dramatically increased the mRNA levels of NF-κB p50 and IKKα in the bladder epithelium of rats compared to the control group. Immunohistochemical examinations showed that DMAV increased immunoreactivities of IKKα, IKKβ, and phospho-NF-κB p50 in the cytoplasm and phospho-NF-κB p50 and p65 in nucleus of rat urothelial cells. In addition, DMAV treated rats exhibited significantly increased inflammatory factor TGF-β immunoreactivity in bladder epithelium and IL-1β secretion in urine. These data suggest that DMAV could activate NF-κB signal pathway and increase TGF-β and IL-1β expressions in bladder epithelial cells of rats.